Ceramics and amorphous thin films based on gallium sulphide doped by rare-earth sulphides. (5th March 2015) - Popescu, M; Sava, F; Lőrinczi, A; Velea, A; Simandan, I D; Badica, P; Burdusel, M; Galca, A C; Matei, E; Preda, N; Secu, M; Socol, G; et al.
Abstract: Bulk ceramics of Ga2 S3 and rare-earth sulfides (EuS, Gd2 S3, Er2 S3 ) as well as combinations thereof have been prepared by spark plasma sintering (SPS). The disk-shaped ceramics were used as targets for pulsed laser deposition (PLD) experiments to obtain amorphous thin films. The properties of these new bulks and amorphous thin films have been investigated by x-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDX), optical transmission spectroscopy, and atomic force microscopy (AFM). In order to test the photoexpansion effect in Ga2 S3 and the possibility to create planar arrays of microlenses, the film was irradiated with femtosecond laser pulses at different powers. For low laser power pulses (up to 100 mW power per pulse) a photoexpansion effect was observed, which leads to formation of hillocks with a height of 40–50 nm. EuS doped Ga2 S3 thin film shows luminescence properties, which recommend them for optoelectronic applications.